The LncRNA RMST-miR-4295-ITPR1 axis: a key mechanism in regulating autophagy in triple-negative breast cancer cells - Linlei Zhang; Sainan Li; Jiajie Shi; Hao Guo; Bo Wang; Cuizhi Geng (BMC Cancer)
Abstract Background Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer with poor prognosis and limited treatment options. Autophagy targeting plays a complex role in tumor resistance. The role of long noncoding RNA (LncRNA) RMST in TNBC progression and its potential involvement in autophagy regulation remain largely unexplored. Methods We performed a bioinformatics analysis using transcriptome sequencing data to identify differentially expressed genes related to autophagy and the LncRNA-miRNA-mRNA axis in TNBC. The effects of the LncRNA RMST-miR-4295-ITPR1 axis on TNBC cell proliferation and migration were investigated using CCK-8, EdU, Transwell, and wound healing assays. Additionally, a series of in vitro experiments, including flow cytometry, transmission electron microscopy, and western blotting, were performed to evaluate the role of the LncRNA RMST-miR-4295-ITPR1 axis in regulating autophagy. Results LncRNA RMST competes with ITPR1 mRNA for miR-4295 binding, thereby relieving the miR-4295-mediated suppression of ITPR1 and increasing ITPR1 expression. Overexpression of LncRNA RMST or ITPR1 significantly inhibited TNBC cell proliferation and migration, promoted apoptosis, and enhanced autophagy. Conversely, miR-4295 overexpression reversed these effects, confirming the regulatory role of the LncRNA RMST-miR-4295-ITPR1 axis in autophagy in TNBC. Conclusions Our findings indicate that the LncRNA RMST-miR-4295-ITPR1 axis plays a crucial role in regulating autophagy in TNBC cells. The modulation of this axis may represent a novel therapeutic strategy for inhibiting TNBC progression and overcoming chemoresistance.